(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describing clinical features and outcomes of close tibia fracture ORIF (open reduction internal fixation) at Vietduc University Hospital Patients and method: Prospective and retrospective studies 54 tibias close fractures were ORIF using Carm from January 2020 to October 2022. Results: Mean ages 41,59 ± 12,89. 52/54 (96,3%) patients were good wound healing. The result of 6 months postoperative was 57,5% excellent and 24,1% good. No patient has malalignment. The excellent result of Xray, according to Rasmusen, was higher in grades I, II, III, IV compared to grades V, VI (p<0,05). Conclusion: ORIF using Carm has excellent functional outcomes in patients with tibia fractures.